2018
DOI: 10.1021/acsami.8b04582
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Intrinsically Stretchable Organic Solar Cells Enabled by Charge-Extraction Layer and Photoactive Material Engineering

Abstract: The rapid development of wearable electronic devices has prompted a strong demand to develop stretchable organic solar cells (OSCs) to serve as the advanced powering systems. However, to realize an intrinsically stretchable OSC is challenging because it requires all the constituent layers to possess certain elastic properties. It thus necessitates a combined engineering of charge-transporting layers and photoactive materials. Herein, we first describe a stretchable electron-extraction layer using a blend of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 39 publications
0
57
0
Order By: Relevance
“…It lagged far behind that of rigid devices fabricated on glass substrates. Hsieh et al demonstrated a stretchable all‐polymer OSC comprising a PEDOT:PSS anode with DMSO and Zonyl treatments and an electron‐extraction layer ( Figure ). The PCBM‐based device fabricated on 3M elastomeric tapes yielded a high PCE of 3.21% and it had an intrinsic stretchability of 5%.…”
Section: Stretchable Electronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It lagged far behind that of rigid devices fabricated on glass substrates. Hsieh et al demonstrated a stretchable all‐polymer OSC comprising a PEDOT:PSS anode with DMSO and Zonyl treatments and an electron‐extraction layer ( Figure ). The PCBM‐based device fabricated on 3M elastomeric tapes yielded a high PCE of 3.21% and it had an intrinsic stretchability of 5%.…”
Section: Stretchable Electronicsmentioning
confidence: 99%
“…Optical microscopy images of the c) PFN and d) PFN/NBR films subjected to 60% strain. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Stretchable Electronicsmentioning
confidence: 99%
“…It could also be assumed that the presence of the ultrathin silica layer that is a metal oxide used as an interlayer in inverted OSCs can improve electron extraction. Several studies have reported that the use of a metal oxide layer as interlayer between the organic layer and the anode/cathode facilitates charge extraction and affords well behaved highly efficient third generation solar cells . In addition, the silica layer might be regarded as a dielectric barrier layer around the MNPs incorporated in the OSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that the use of a metal oxide layer as interlayer between the organic layer and the anode/cathode facilitates charge extraction and affords well behaved highly efficient third generation solar cells. [35][36][37][38][39][40] In addition, the silica layer might be regarded as a dielectric barrier layer around the MNPs incorporated in the OSCs.…”
Section: Resultsmentioning
confidence: 99%
“…[271] Inherently Stretchable OPVs: Although buckling enables stretchability, the layers are prone to delamination at the interface upon repetitive stretching, which reduces the lifetime of the device. [272] An inherently stretchable solar cell can enable mechanical durability and long-term stability. This can be done by plasticizing the organic semiconductor (using additives).…”
Section: Organic Photovoltaics (Opvs)mentioning
confidence: 99%